Conceptualizing Microfinance Initiatives in India Using SAP-LAP Model:A New Paradigm in Marketing Engineering - Chaudhuri, Ranjan; Sushil; Patil, Pravin (Indian Journal of Marketing, 2009)
One of the major focuses of the United Nations Millennium Development Goals (MDGs) is to partially alleviate world’s poverty by 2015. Leveraging upon its demographic dividend India is strategically poised to realize the MDGs. One way to create wealth at the bottom of the pyramid is to ensure availability and access to transparent credit facilities to the poorest sections of the Indian society. More than subsidies poor need access to credit. Absence of formal employment makes them ’non-bankable.’ This forces them to borrow from local moneylenders at exorbitant interest rates. Many innovative institutional mechanisms have been developed across the world to enhance credit to poor even in the absence of formal mortgage. Drawing insights from the domain of microfinance market in India, this article conceptualizes the SAP-LAP model of a microfinance institution in India.